2020
DOI: 10.3390/ijms21165661
|View full text |Cite
|
Sign up to set email alerts
|

Orchestration of Intracellular Circuits by G Protein-Coupled Receptor 39 for Hepatitis B Virus Proliferation

Abstract: Hepatitis B virus (HBV), a highly persistent pathogen causing hepatocellular carcinoma (HCC), takes full advantage of host machinery, presenting therapeutic targets. Here we aimed to identify novel druggable host cellular factors using the reporter HBV we have recently generated. In an RNAi screen of G protein-coupled receptors (GPCRs), GPCR39 (GPR39) appeared as the top hit to facilitate HBV proliferation. Lentiviral overexpression of active GPR39 proteins and an agonist enhanced HBV replication and transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 89 publications
0
3
0
Order By: Relevance
“…These candidates were further tested for their effect against the Rift Valley Fever Virus (RVFV) and Herpes Simplex Virus (HSV-1). Depletion of GPR39, a regulator of heat shock proteins and the hedgehog pathway [ 35 ], showed highly virus-specific effects: While GRP39 depletion increased SARS-CoV-2 replication, it decreased the propagation of all other viruses tested ( Figure 1 B–F). Better growth of SARS-CoV-2 and VSV was seen upon knockout of SLC30A1 ( Figure 1 B,C), which has been reported to elevate intracellular zinc levels and hence inhibit caspase activation and apoptosis [ 36 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…These candidates were further tested for their effect against the Rift Valley Fever Virus (RVFV) and Herpes Simplex Virus (HSV-1). Depletion of GPR39, a regulator of heat shock proteins and the hedgehog pathway [ 35 ], showed highly virus-specific effects: While GRP39 depletion increased SARS-CoV-2 replication, it decreased the propagation of all other viruses tested ( Figure 1 B–F). Better growth of SARS-CoV-2 and VSV was seen upon knockout of SLC30A1 ( Figure 1 B,C), which has been reported to elevate intracellular zinc levels and hence inhibit caspase activation and apoptosis [ 36 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Later, it has been shown to activate all GPR39 inducible pathways [ 35 ]. Since its discovery, TC-G 1008 has proven to be a potent agonist and a very valuable tool in characterizing the physiological functions and therapeutic potential of GPR39 activation, published by a number of studies to date [ 30 , 31 , 32 , 35 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 ]. However, most studies have not verified their findings in GPR39 −/− settings, which would be critical in order to confirm that the observed effects are indeed GPR39-dependent.…”
Section: Ligands Of Gpr39mentioning
confidence: 99%
“…Interestingly, one study indicated GPR39 activation in hepatitis B virus proliferation. GPR39, activated by TC-G 1008, was shown to induce the transcription of viral promoters and proviral heat shock proteins, suggesting that GPR39 inhibition could be studied as a novel strategy to combat viral replication in cells [ 66 ].…”
Section: Physiological Functions Of Gpr39mentioning
confidence: 99%